Linguistique et iconographie des cartes publicitaires - Laurence Kister; Renaud Lallement (Communication)
Advertising cards, whether they complete other media or constitute a complimentary advertising campaign, rest on either language or on language and the visual. The analysis examines the linguistic proceedings — particularly, rhetorical figures — and the links these establish between text and illustration. The observations are of cards wherein the advertising arguments use text and illustration and cards, which privilege linguistic aspects. The results show figures where illustration and text are indispensable to an accurate interpretation of the message, and others where the text suffices to understand, and still others, which necessitate cultural references in order to be understood.